Hubungan Pola Kebersihan Diri Dengan Terjadinya Gangguan Kulit Pada Petani Padi - Septina Riyansari; Irdawati Irdawati (Universitas Muhammadiyah Surakarta, 2018)
One of the jobs that is vulnerable to skin disorders is farmers. So that research is needed to see patterns of personal hygiene in farmers. The purpose of this study was to determine the relationship between patterns of personal hygiene with the occurrence of skin disorders in rice farmers in the Nanggulan Village Work Area Cawas I Health Center, Cawas District, Klaten Regency. This research is non-experimental quantitative research that is an analytic survey with cross-sectional design. The population in this study was 767 people and the sample obtained by 89 respondents. Sampling is done by stratified random sampling technique by proportional random sampling. From the results showed a significant relationship between patterns of personal hygiene with the occurrence of skin disorders with a P-value of 0.001 and = 10.426. The conclusion of this study is that there is a relationship between patterns of personal hygiene with the occurrence of skin disorders in rice farmers in the Nanggulan